The Ibanag teacher their characteristics, expressed professional problems and aspirations - Mangawil, Crispina Z. (s.n.], 1972)
The characteristics, problems, and aspirations of the Ibanag Elementary School teachers of Tuguegarao Districts I and II of Cagayan I were determined in this study.